GREEN SUPPLY CHAIN: ASSOCIATIONS AMONG DRIVERS, PRACTICES AND PERFORMANCE - Goularte, Gustavo Neves; Dias, Marcelo Fernandes Pacheco (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The research objective was to analyze external and internal drivers, green practices and economic and environmental performance in a green supply chain management – GSCM. The motivation of the study lies in the limited number of studies on how the elements of a GSCM associate with one another and especially in the port sector. To meet this objective, a case study was carried out in the green supply chain of the Container Terminal of the Port of Rio Grande. As a result, it was possible to identify a complex system of parts (external drivers, internal, practices and performance indicators) and associations involving the studied GSCM. There was evidence of specific associations between drivers and practices and between practices and GSCM performance indicators. There are practices that contribute to both performances. External drivers can directly condition the presence of performance indicators.